Sustainable Energy and the Second Law of Thermodynamics: An Introduction to the Special Issue - Hathaway, George; Sheehan, Daniel P. (Journal of Scientific Exploration, 2022)
At the end of the 19th century, the ﬁeld of physics was considered nearly complete, encouraging triumphal statements by some of the most eminent physicists of the day, for instance, "There is nothing new to be discovered in physics now. All that remains is more and more precise measurement (William Thompson, Baron Kelvin of Largs). Only a few random clouds troubled this bright horizon, for instance, the vexing negative result of the Michelson-Morley experiment, some puzzling aspects to the photoelectric eﬀect, and a the lack of a coherent explanation for the blackbody radiation spectrum. Nothing terribly serious, nothing that wouldn’t be mopped up eventually. In fact, the ﬁrst would soon be key to Einstein’s revolutionary special theory of relativity, the second would win him the Nobel prize in physics, and the third, in the able hands of Max Planck, would crack open the door to the paradigm-shattering quantum world. Indeed, every moment is the end of physics or its beginning-–depending on one’s curiosity. Viewed through the lens of Thomas Kuhn’s The Structure of Scientiﬁc Revolutions, physics’ sudden turnabout was to be expected. Whenever experts consider a ﬁeld complete, beware and be amused, for it will likely erupt in revolution. This is because the nature of knowledge itself guarantees scientiﬁc paradigms will invariably germinate the seeds of their own destructions. They must. When a paradigm is established, it is encumbent upon scientists to explore it as fully as possible, to extend its domain to the fullest possible extent.